The waterbirds of Pulau Rambut, Java - Frank Lambert; Paul Erftemeijer (Indonesian Ornithologists’ Union, 1989)
Pu1au Rambut, in the Seribu Archipelago, Jakarta Bay (5° 38'S, 106° 42'E)is a small (25 ha) forested coral atoll which has been a nature reserve since 1937. Its present status is a strict Nature Reserve (Cagar A1am), and it has been identified as one of the most Important waterbird breeding sites of Java (Silvius et a1. 1987). About half the Island's vegetation is tidal mangrove, dominated by Rizophora spp., but the southern part of the Island 1s covered with dryland forest with a tree canopy reaching 20 m. The south and south of the island is bordered by a narrow strip of dry beach forest dominated by Casuarina equisetifolia. A comprehensive description of the vegetation is provided by Kartawinata & Waluyo (1977: see also Figure 1).The authors, with Pandu Hartoyo from the Indonesian Directorate General of Forest Protection and Nature Conservation (PHPA) visited P. Rambut between11 and 14 January 1987. During this period rough estimates were made of the numbers of waterbirds present on the island, with a brief assessment of the threats to the nesting waterbird colony. This paper is a summary of our findings and a review of literature on the waterbirds of P. Rambut.